LatitudeTM Oil as a Sustainable Alternative to Dietary Fish Oil in Rainbow Trout (Oncorhynchus mykiss): Effects on Filet Fatty Acid Profiles, Intestinal Histology, and Plasma Biochemistry - Hong, Jeongwhui; Bledsoe, Jacob W.; Overturf, Kenneth E.; Lee, Seunghan; Iassonova, Diliara; Small, Brian C. (Frontiers in Sustainable Food Systems, 2022)
The aim of this study was to evaluate the effects of Latitude™ oil (transgenic canola) fed to rainbow trout, Oncorhynchus mykiss, for 52 weeks on growth performance, non-specific immune responses, histology, and filet omega-3 fatty acid content. Latitude™ oil (LO) has high lipid digestibility (93%), and contains omega-3 fatty acids eicosapentaenoic acid (EPA, C20:5n-3), docosapentaenoic acid (DPA, C22:5n-3), and docosahexaenoic acid (DHA, C22:6n-3). Three isonitrogenous (49%), isolipidic (20%) and isocaloric (24.2 MJ kg−1) diets differing by lipid source (0, 8, or 16% LO, replacing fish oil and poultry fat) were fed over an entire production cycle beginning with 19 g juvenile fish. At the end of the 52-week feeding trial, final body weight, weight gain and specific growth rate of fish fed 8% LO (LO-8) and 16% LO (LO-16) diets were significantly higher than those fed the 0% LO (LO-0) diet (P < 0.05). Phagocytic respiratory burst in fish fed the LO-16 diet was significantly higher than those fish fed the other 2 diets (P < 0.05). There were no differences in superoxide dismutase, catalase and lysozyme. Histological examination of the distal intestine indicated reduced inflammation in fish fed the LO-8 diet but not the LO-0 and LO-16 diets. Filet DHA content of fish fed the LO-8 and LO-16 diets were similar to those of fish fed the LO-0 diet. As these diets had lower DHA content, this suggests dietary EPA and DPA from LO was converted to DHA and deposited in the filet. This is supported by increased expression of genes involved in fatty acid elongation, desaturation and beta oxidation in both liver and muscle of fish fed LO (P < 0.05). Total EPA+DHA content of the edible filet ranged between 1,079–1,241 mg 100 g−1 across treatments, each providing the recommended daily intake for human consumption (500–1,000 mg day−1). Overall, this study demonstrated that LO fed over an entire production period is a highly digestible lipid source suitable and sustainable for meeting the fatty acid requirements of rainbow trout, as well as consumer expectations for filet omega-3 fatty acid content.